2022
DOI: 10.1001/jamanetworkopen.2022.10724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mailing an At-home Disposal Kit on Unused Opioid Disposal After Surgery

Abstract: This randomized clinical trial tests the effect of a mailed, at-home disposal kit on disposal rates of unused opioids after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…Our disposal rate of 26.4% was lower than most prior disposal bag studies which reported rates of 55%–95% 32–36 . Several factors likely contribute to this lower rate of disposal.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Our disposal rate of 26.4% was lower than most prior disposal bag studies which reported rates of 55%–95% 32–36 . Several factors likely contribute to this lower rate of disposal.…”
Section: Discussioncontrasting
confidence: 69%
“…Prior studies by our group and others suggest that providing postoperative home‐disposal bags resulted in 55%–95% of patients disposing of their leftover opioids 32–36 . However, a subsequent trial showed disappointing results, with only 14% of patients disposing of their opioids 37 .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the Research Letter titled “Effect of Mailing an At-home Disposal Kit on Unused Opioid Disposal After Surgery: A Randomized Clinical Trial,” 1 published May 6, 2022, Mary Coniglio’s surname was misspelled in the byline and author affiliations. This article has been corrected.…”
mentioning
confidence: 99%